ANALISIS BALANCED SCORECARD PADA RSUP X PALEMBANG - Aries Veronica; Karnold A. Siahaan (KOLEGIAL, 2013)
This study purpose analyzed in applied of balanced scorecard at RSUP X Palembang. Beside compare the dimension method through the traditional approach by the balanced scorecard. The research has done at RSUP X in palembang with using the seconder data on 2011-2012. Balanced scorecard as the main system of management strategy has four superiors, namely : motivated personal to think and act the strategy will be carry to aim the company to the future. Based on the demension of four perspectives are look like that the first place is installation of the treatment stay has best method, the second place is installation of the children health treatment stay, the third place is obstetrics, the fourth place is the installation of surgery treatment stay, the fifth is the installation of non surgery treatment stay and the last one is the installation of intensive treatment stay. The hospital RSUP X Palembang will be the best hospital in south sumatera which has to rise are : Human resources, sorrounding, safety/quietude, attendance, purity, rooms for the patient, parking place, buildings, rules of the proper conduct for the visitors, facility of equipments (bed, bathroom, air circulation etc).